Serum protein profile analysis via label-free quantitation proteomics in patients with early-onset preeclampsia - Qinghong Ji; Shulin Zhang; Wen Jiang; Jue Wang; Yun Luan; Qian Xin (Journal of Obstetrics and Gynaecology, 2023)
Background Preeclampsia (PE) is a serious pregnancy complication, resulting in potentially life-threatening conditions for both mother and foetus. It is worth noting that early-onset PE has become a great challenge for clinicians due to its complex manifestation, rapid progression and serious complications. This study aims to investigate differential serum proteome profiles in patients with early-onset PE. Methods Each serum sample was separated using a nanoliter flow rate Easy-nLC chromatography system. Then the samples were analysed by mass spectrometry. Bioinformatics analyses were conducted to analyse the functional categories or signal transduction pathways for differentially abundant proteins. Key proteins identified by mass spectrometry were verified by ELISA. Results We found 30 and 34 proteins were upregulated and downregulated in early-onset PE patients (n = 3) vs controls (n = 3), respectively. Functional enrichment analysis revealed differentially expressed proteins related to the immune response and regulation of peptidase activity. ELISA confirmed that there were lower CSH1 levels and higher LPA concentrations in the serum samples of early-onset PE patients (n = 22) than in healthy controls (n = 19) (p < 0.05 for CSH1 and p < 0.001 for LPA). Conclusions This study revealed the critical features of serum proteins in early-onset PE patients. LPA and CSH1 may serve as biomarkers for early-onset PE diagnosis and therapy.